WEBSITE-BASED DIGITAL MODULE ACCEPTANCE WITH MERDEKA FLOW STRATEGY IN ELEMENTARY SCHOOLS IN BANDUNG CITY AREA - Ahmad Solihin; Dede Margo Irianto; Yusuf Tri Herlambang (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of technology in the 21st century is accompanied by the widespread use of digital technology to support human activities in various fields. Likewise in learning activities, the use of technology in learning is a necessity. Integration of technology in learning can be in the form of using technology as a learning medium in the form of digital modules. This study aims to analyze the effect of the independent flow strategy on the acceptance of website-based digital modules, as well as its effect on Effort Expectancy Behavior Intention (media use efforts) and Facilitating Condition (facilitating support). This study uses a quantitative approach with correlational survey methods and path analysis. Data was collected from 118 teachers in Bandung City. The results of the study indicate that the independent flow strategy has a positive and significant effect on the acceptance of website-based digital modules, Effort Expectancy Behavior Intention, and Facilitating Condition. This result is shown by looking at the 10 indicators that determine the acceptability of teaching materials and media. There are indicators of Effort Expectancy Behavior Intention (effort to use media) and Facilitating Condition (supporting facilities) that determine the acceptability and good influence on the media created. This finding shows that the independent flow strategy can increase the acceptance of website-based digital modules, motivate users to use media, and provide convenience for users in accessing and learning learning materials.